Monobutyl and Monophenyl Substituted Tin Derivatives of N-(o-Hydroxy Substituted Benzyl) Alanines - Gangwar, Tripti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several monobutyl and monophenyl substituted tin derivatives of N-(o-hydroxy substituted benzyl) alanines have been prepared by alcoholysis reactions. The various compounds thus prepared were generally obtained as coloured solids and amongst them those containing isopropoxy group were found to be hygroscopic. All these compounds were characterized by azeotrope and elemental analyses, as well as by IR and PMR spectral measurements.